The Role of Mitophagy in Hereditary Optic Neuropathies. Literature Review - Andreeva, N. A.; Sheremet, N. L.; Murakhovskaya, Yu. K.; Dayal, A. A.; Minin, A. A. (Oftalmologii͡a, 2021)
The role of mitophagy in hereditary optic neuropathies is considering in this review. Mitochondria are intracellular double membrane organelles. They are one of the main components of all eukaryotic cells, they perform many different functions in the cell. However, the main function of mitochondria is to supply cells with energy in the form of ATP. The ATP synthesis is carried out due to the respiratory chain five protein complexes work, the main components of the chain are located in the inner mitochondrial membrane. It is known that proteins that form all respiratory chain complexes (except II) are encoded by both nuclear and mitochondrial genes. The mitochondrial electron transport chain dysfunction leads to the mitochondrial diseases development, which can be a result of mutations both in mtDNA and in nDNA. The most common eye mitochondrial diseases are hereditary optic neuropathies (HON), such as Leber Hereditary Optic Neuropathy (LHON). The main cause leading to the disease are mtDNA mutations. These mutations lead to the respiratory chain complexes dysfunction (mainly I), which results in mitochondrial damage. To remove damaged mitochondria in time, cells have special regulatory systems. These systems are responsible for the damaged mitochondria detection, isolation and degradation through a specific form of autophagy, mitophagy. For normal functioning, cells need to maintain a constant balance between mitochondrial biogenesis and mitophagy. A violation of this balance leads to the disease. It was revealed that mitophagy, an important retinal ganglion cells protection mechanism, is impaired in patients with LHON. The mitophagy activation may have the therapeutic potential. Some pharmacological agents activate mitophagy and thereby slow down the disease development in patients with hereditary optic neuropathies, such as LHON. Some of them, such as rapamycin, trehalose, metformin, spermidine, NAD + , are described in the review.